Review on surgical management of ptosis and the use of phenylephrine: A national survey of British Oculoplastic Surgery Society (BOPSS) UK Consultants. (1st November 2016) - Mota, Peter M.; Norris, Jonathan H.
ABSTRACT: We assess current practice using topical phenylephrine by British Oculoplastic Surgery Society (BOPSS) consultants in the surgical management of ptosis. All UK consultant BOPSS members were invited to participate in a web-based survey, consisting of 8 questions relating to the surgical management of adult primary involutional ptosis with normal levator function and the use of phenylephrine in the management of ptosis. 53 BOPSS consultants (43%) completed the survey, of which 76% perform anterior approach levator advancement as first-line surgery. Then, 40% of consultants routinely use phenylephrine unilaterally in the ptotic eye, with 90% using 2.5% as opposed to 10%. Also, 77% of consultants use topical phenylephrine to illustrate the predicted outcome of surgery for the patient's benefit and 65% modify their approach on the basis of the test. If phenylephrine raises the ptotic eyelid >2 mm, those using an anterior approach reduces to 13.6%, with majority using a posterior approach (86.4%). If phenylephrine induces no improvement, then 76% use an anterior approach. If phenylephrine induces a contralateral ptosis 79% of consultants will perform simultaneous bilateral surgery. A number of interesting trends were observed amongst BOPSS consultants in their surgical approach to ptosis based on the phenylephrine test. The majority of consultants will switch from anterior to posterior approach surgery when the phenylephrine test is strongly positive and will also perform bilateral surgery when a contralateral ptosis is induced with phenylephrine.